A Hospital Based Crosssectional Study on Early and Late onset Psoriatic Patients - E, Deepthi; S, Vijayakumar; D, Ramchander (Indian Journal of Pharmacy Practice)
Psoriasis is a common, chronic disfiguring inflammatory disease of the skin characterized in most cases by well defined scaly, red and indurate plaques mainly over extensor surfaces but also often involving other areas of the body. Although there are several studies investigating oxidant/antioxidant systems and lipid profile in psoriatic patients, the data obtained from these studies is not concordant. In this study, Malondialdehyde (MDA), Glutathione (GSH), Total antioxidant status (TAS) in fourty patients with psoriasis were investigated and compared with those of forty Control subjects. Clinical severity of the disease was determined according to the Psoriasis Area and Severity Index (PASI) scores in the patients. Plasma MDAlevels were significantly higher (p= 0.0119) whereas TAS and GSH levels were lower, in patients than control subjects (p= 0.0001 and p= 0.0001 respectively). There was no correlation between PASI scores and plasma MDA, GSH, TAS levels. Our findings may provide some evidence for a potential role of increased ROS production and decreased antioxidant activity in psoriasis. Whereas, serum Albumin and Calcium levels in psoriatic patients were found to be lower than control subjects.